Assessment of drought in Shipra River Basin, Madhya Prade - JAISWAL, SMITA; GALKATE, RAVI; CHANDOLA, V. K.; SINGH, PRASHANT; THAKUR, ARADHANA (Journal of Soil and Water Conservation, 2020)
Drought is a most common natural hazard which can be characterized by using meteorological as well as hydrological data. To quantify the drought condition and combat them, interrelationships between meteorological and hydrological are necessitate. In present study drought situation were assessed for the Shipra basin as the recurrence of drought in these parts of the country in recent years have triggered unprecedented economic losses and great suffering to the affected areas. The mean annual rainfall of Shipra basin is estimated as 931 mm. The analysis results shown that the year 1965, 1972 and 2000 were most severely affected drought years in the basin as most of the area of the basin was under drought. From the study it has concluded that the Shipra basin experiences one drought year after every 4 to 5 years and almost all the basin comes under drought prone area.